Visualizing the neuronal transcriptional landscape with tissue context - Agudelo Duenas, Nathalie
Spatial omics technologies are enriching our understanding of complex biological samples, by allowing us to study their molecular composition while preserving the spatial relationships between molecules in their native context. As the field continues to advance, there are technical challenges that need to be addressed in order to take full advantage of the spatial capabilities of these methods. In this work, I present two technical developments that I established for multiplexed error robust FISH (MERFISH) throughout my PhD: (1) pushing the spatial resolution limits to the nanoscale, and (2) adding rich tissue context to the mouse brain transcriptome. To achieve nanoscale resolution with MERFISH in cultured cells, I combined it with stimulated emission depletion (STED) and expansion microscopy (ExM) to achieve a spatial resolution as low as ~20 nm, and explored the compatibility of MERFISH with singlemolecule localization microscopy (SMLM) techniques. To visualize targeted mRNAs in mouse brain tissue, I applied the comprehensive analysis of tissues across scales (CATS) toolbox, which provides an unbiased morphological readout by labeling the extracellular domain. I successfully established this method, which we call CATS-MERFISH-ExM, to work with thick mouse brain slices, being able to extract transcriptomics information with 3D tissue context. CATS-MERFISH-ExM enabled us to identify cell types and further visualize the subcellular distribution of transcripts in mouse brain tissue, shedding light on the neuropil-specific transcriptome. This method provides integrated information on cellular structure and transcriptomes in situ, and could potentially be applied with other modalities, opening new avenues for scientific discovery.

Strong charge-photon coupling in planar germanium enabled by granular aluminium superinductors - Janik, Marian; Roux, Kevin Etienne Robert; Borja Espinosa, Carla N; Sagi, Oliver; Baghdadi, Abdulhamid; Adletzberger, Thomas; Calcaterra, Stefano; Botifoll, Marc; Manjón, Alba Garzón; Arbiol, Jordi; Chrastina, Daniel; Isella, Giovanni; et al. (arXiv)
High kinetic inductance superconductors are gaining increasing interest for the realisation of qubits, amplifiers and detectors. Moreover, thanks to their high impedance, quantum buses made of such materials enable large zero-point fluctuations of the voltage, boosting the coupling rates to spin and charge qubits. However, fully exploiting the potential of disordered or granular superconductors is challenging, as their inductance and, therefore, impedance at high values are difficult to control. Here we have integrated a granular aluminium resonator, having a characteristic impedance exceeding the resistance quantum, with a germanium double quantum dot and demonstrate strong charge-photon coupling with a rate of $g_\text{c}/2π= (566 ± 2)$ MHz. This was achieved due to the realisation of a wireless ohmmeter, which allows in situ measurements during film deposition and, therefore, control of the kinetic inductance of granular aluminium films. Reproducible fabrication of circuits with impedances (inductances) exceeding 13 k$Ω$ (1 nH per square) is now possible. This broadly applicable method opens the path for novel qubits and high-fidelity, long-distance two-qubit gates.

Everyday electromechanics: Capacitive strong coupling to mechanical motion - Puglia, Denise
We introduce a new all-electric platform, that strong couples light to mechanical motion by ensuring that the external environmental coupling dominates over internal mechanical dissipation. The system only has three everyday components: AC, DC, and a fip-chip, in which a metallized silicon nitride membrane is fipped on top of the device under test. This everyday electromechanical device can be operated at low or room temperature and has 10000× lower insertion loss than a comparable commercial quartz crystal, achieves a position imprecision matching state-of-the-art optical interferometer, and enables remote cooling of mechanical motion. The spatial properties of higher order mechanical modes are a promising feature for reconstructing unknown charge distributions.

Room temperature, cavity-free capacitive strong coupling to mechanical motion - Puglia, Denise; Odessey, Rachel H; Burns, Peter S.; Luhmann, Niklas; Schmid, Silvan; Higginbotham, Andrew P (arXiv)
Strong optomechanical coupling -- a regime where mechanical motion is damped by environmental radiation -- has traditionally required demanding experimental ingredients such as superconducting resonators, high-quality optical cavities, or large magnetic fields. Here we demonstrate a room temperature, cavity-free, all-electric device reaching this regime at radio frequencies, enabled by a mechanically compliant parallel-plate capacitor with a nanoscale plate separation and an aspect ratio exceeding 1,000. The device has four orders of magnitude lower insertion loss than a comparable commercial quartz crystal, and achieves a position imprecision rivaling an optical interferometer. With the help of a back-action isolation scheme, we observe radiative cooling of mechanical motion by a remote cryogenic load. This work provides a technologically accessible route to high-precision sensing, transduction, and signal processing.

Dual relaxation oscillations in a Josephson junction array - Mukhopadhyay, Soham; Lancheros Naranjo, Diego A; Senior, Jorden L; Higginbotham, Andrew P (arXiv)
We report relaxation oscillations in a one-dimensional array of Josephson junctions. The oscillations are circuit-dual to those ordinarily observed in single junctions. The dual circuit quantitatively accounts for temporal dynamics of the array, including the dependence on biasing conditions. Injection locking the oscillations results in well-developed current plateaux. A thermal model explains the relaxation step of the oscillations.

Visual adaptations to natural statistics - Gupta, Divyansh
Biological vision is unlike a camera; rather than transmitting light information faithfully, early visual circuits process the visual scene to convey only the relevant information in an efficient manner. Consequentially, the nature of this visual processing then depends on what is the relevant information in a scene and on the notion of efficiency. In this work, I study how visual processing is modulated by two different variations in the visual scene. First, I discovered that in the mouse (Mus musculus) retina, Retinal Ganglion Cells in the upper and lower visual field have differences in the center surround structure of their receptive fields. Comparison with models of efficient coding show that this adaptation likely evolved to cope with the brightness gradient from the sky to the ground that is pervasive in natural scenes. In the second project, I study how the downstream neurons in the Superior Colliculus dynamically change their temporal selectivity depending on the ambient luminance and behavioral state. As the scene gets darker or when the animal is is less aroused, the neuronal responses get laggier, while still maintaining their relative timing with respect to the population. Overall, this work emphasises the need to understand visual processing in the context of specific demands of the animal in its the environment. The adaptive changes in the visual system, from the retinal ganglion cells to the superior colliculus, highlight the intricate ways in which biological vision optimizes the processing of visual information.

Early stages of sex chromosome evolution - Mrnjavac, Andrea
Sex chromosomes and autosomes exhibit very different evolutionary dynamics. The Y chromosome usually degenerates, leaving many X-linked loci hemizygous in males. Since recessive X-linked mutations are always exposed to selection in males, selection is more efficient on the X chromosome than on autosomes on recessive mutations, leading to faster adaptation on the X chromosome than other genomic regions, if beneficial mutations are on average recessive (known as the Faster-X effect). In the presence of the functional, but non-recombining gametolog on the Y (as is often the case in young non-recombining regions), recessive mutations are sheltered from selection on the X chromosome. We model this scenario and show that the efficiency of selection is reduced on diploid X loci due to sheltering by the Y chromosome. Reduced efficiency of selection leads to slower adaptation and increased accumulation of deleterious mutations (Slower-X effect). We extended this model to explore the effect of sex-specific selection on degeneration of sex chromosomes, showing theoretically that male-limited genes degenerate on the X chromosome and female-biased genes degenerate on the Y chromosome. This prediction depends on the effective population size and the mutation rate, explaining the variety of sex chromosome degeneration patterns observed in nature. To test for direct evidence of a Slower-X (or Slower-Z) effect, we analyzed the ZW sex chromosomes of the flatworm Schistosoma japonicum, which have a very young non-recombining region with non-degenerated W. Diploid Z-linked genes have higher ratios of non-synonymous to synonymous polymorphisms than autosomal genes, supporting reduced efficiency of selection on the diploid Z region. These results provide evidence of sheltering by the W chromosome, a mechanism that could contribute to Z (X) chromosome degeneration, and illustrate contrasting evolutionary patterns in old and young sex chromosome regions. In addition, genes with sexspecific patterns of expression show opposite patterns of selection in the young (diploid) and old (hemizygous) Z, showing the complex manner in which sex-specific selection shapes the evolutionary patterns of sex chromosomes.
Keywords: Sex chromosomes; evolution; selection; sheltering

Evidence of a Slower-Z effect in Schistosoma japonicum - Mrnjavac, Andrea; Vicoso, Beatriz (bioRxiv)
Sex-linked and autosomal loci experience different selective pressures and evolutionary dynamics. X (or Z) chromosomes are often hemizygous, as Y (or W) chromosomes often degenerate. Such hemizygous regions can be under greater efficacy of selection, as recessive mutations are immediately exposed to selection in the heterogametic sex (the so-called Faster-X or Faster-Z effect). However, in young non-recombining regions, Y/W chromosomes often have many functional genes, and many X/Z-linked loci are therefore diploid. The sheltering of recessive mutations on the X/Z by the Y/W homolog is expected to drive a Slower-X (Slower-Z) effect for diploid X/Z loci, i.e. a reduction in the efficacy of selection. While the Faster-X effect has been studied extensively, much less is known empirically about the evolutionary dynamics of diploid X or Z chromosomes. Here, we took advantage of published population genomic data in the female-heterogametic human parasite Schistosoma japonicum to characterize the gene content and diversity levels of the diploid and hemizygous regions of the Z chromosome. We used different metrics of selective pressures acting on genes to test for differences in the efficacy of selection in hemizygous and diploid Z regions, relative to autosomes. We found consistent patterns suggesting reduced Ne, and reduced efficacy of purifying selection, on both hemizygous and diploid Z regions. Moreover, relaxed selection was particularly pronounced for female-biased genes on the diploid Z, as predicted by Slower-Z theory.

Archaeal membranes : In silico modelling and design - Santana de Freitas Amaral, Miguel
Across the tree of life, distinct designs of cellular membranes have evolved that are both stable and flexible. In bacteria and eukaryotes this trade-off is accomplished by single-headed lipids that self-assemble into flexible bilayer membranes. By contrast, archaea in many cases possess both bilayer and double-headed, monolayer spanning bolalipids. This composition is believed to enable extremophile archaea to survive harsh environments. Here, through the creation of a minimal computational model for bolalipid membranes, we discover trade-offs when forming membranes using lipids of a single type. Similar to living archaea, we can tune the stiffness of bolalipid molecules. We find that membranes made out of flexible bolalipid molecules resemble bilayer membranes as they can adopt U-shaped conformations to enable higher curvatures. Conversely, rigid bolalipid molecules, like those found in archaea at higher temperatures, preferentially take on a straight conformation to self-assemble into liquid membranes that are stable, stiff, prone to pore formation, and which tear during membrane reshaping. Strikingly, however, our analysis reveals that it is possible to achieve the best of both worlds – membranes that are fluid, stable at high temperatures and flexible enough to be reshaped without leaking – through the inclusion of a small fraction of bilayer lipids into a bolalipid membrane. Additionally, the curvature-dependent softening of bolalipid membranes made of lipids with tension-sensitive conformation can also enable high rigidity at low curvatures while softening at high curvatures, making the membrane effectively a plastic material. Taken together, our study compares the different membrane designs across the tree of life and indicates how combining lipids can be used to resolve trade-offs when generating membranes for (bio)technological applications.

Algorithms for causal learning and comparative analysis for genomic data - Machnik, Nick N
This thesis consists of two pieces of work in the broader feld of computational biology, both of which are methods for the analysis of large scale biological data, implemented in efcient software. Chapter 2 introduces a statistical software for causal discovery and inference from observed genetic marker and phenotypic trait data. We explore in simulation how well the method can fne-map genetic efects, fnd the correct causal structure among tens of traits and millions of genetic markers, and infer the causal efect size for the discovered causal relations. We then apply the method to 8 million markers and 17 traits from the UK Biobank and show that many relationships found with other methods are likely due to the efects of hidden confounders. Chapter 3 describes how this method can be applied to longitudinal data. I show how one can incorporate the background knowledge present in the known order of measurements to improve the accuracy of the causal discovery process, and explore the method’s ability to identify age specifc genetic efects, and how the error rates of this recovery are infuenced by missing data due to diferent censoring mechanisms. Chapter 4 introduces a statistical software for the comparison of chromatin contact maps based on the structural similarity index. We explore the robustness of the method to noise and size diferences of the compared maps, show how it can measure evolutionary conservation of topological features by providing a similarity ranking of syntenic regions, and fnally how it can detect alterations in 3D genome structure due to genetic mutations in samples of medical relevance.

Causal inference for multiple risk factors and diseases from genomics data - Machnik, Nick N; Mahmoudi, Seyed Mahdi; Borczyk, Malgorzata; Krätschmer, Ilse; Bauer, Markus J.; Robinson, Matthew Richard (bioRxiv)
Statistical causal learning in genomics relies on the instrumental variable method of Mendelian Randomization (MR). Currently, an overwhelming number of MR studies purport to show causal relationships among a wide range of risk factors and outcomes. Here, we show that selecting instrument variables from genome-wide association study estimates leads to high false discovery rates for many MR approaches, which can be greatly reduced by employing a graphical inference approach which: (i) explicitly tests instrumental variable assumptions; (ii) distinguishes direct from indirect factors in very high-dimensional data; (iii) discriminates pleiotropic from trait-specific markers, controlling for LD genome-wide; (iv) accommodates rare variants and binary outcomes in a principled way; and (v) identifies potential unobserved latent confounding. For 17 traits and 8.4M variants recorded for 458,747 individuals in the UK Biobank, we show that standard MR analysis gives an abundance of findings that disappear under stringent assumption checks, with many relationships reflecting potential unmeasured confounding. This implies that mixtures of temporal precedence and potential for reverse-causality prohibit understanding the underlying nature of phenotypic and genetic correlations in biobank data. We propose that well-curated longitudinal records are likely needed and that our approach provides a first-step toward robust principled screening for potential causal links.

Stability vs flexibility: Reshaping archaeal membranes in silico - Santana de Freitas Amaral, Miguel; Frey, Felix F; Jiang, Xiuyun; Baum, Buzz; Šarić, Anđela (bioRxiv)
Across the tree of life, distinct designs of cellular membranes have evolved. In bacteria and eukaryotes single-headed lipids self-assemble into flexible bilayer membranes. By contrast, archaea often possess double-headed, monolayer spanning bolalipids, mixed with bilayer lipids, enabling them to survive in harsh environments. Here, using a minimal computational model for bolalipid membranes, we discover trade-offs when forming membranes. We find that membranes made out of flexible bolalipids resemble bilayer membranes as bolalipids exhibit conformational switch into U-shaped conformations to enable higher curvatures. Conversely, stiffer bolalipids, resembling those in extremophile archaea, take on straight conformations and form liquid membranes that are stiff, and prone to pore formation during membrane reshaping. Strikingly, we show how to achieve fluid bolalipid membranes that are both stable and flexible – by including small amounts of bilayer lipids, as archaea do. Our study explains how different organisms resolve trade-offs when generating membranes of desired material properties.

The genetic basis of a recent transition to live-bearing in marine snails - Stankowski, Sean; Zagrodzka, Zuzanna B.; Garlovsky, Martin D.; Pal, Arka; Shipilina, Daria; Garcia Castillo, Diego Fernando; Lifchitz, Hila; Le Moan, Alan; Leder, Erica; Reeve, James; Johannesson, Kerstin; Westram, Anja M; et al. (Science)
Key innovations are fundamental to biological diversification, but their genetic basis is poorly understood. A recent transition from egg-laying to live-bearing in marine snails (Littorina spp.) provides the opportunity to study the genetic architecture of an innovation that has evolved repeatedly across animals. Individuals do not cluster by reproductive mode in a genome-wide phylogeny, but local genealogical analysis revealed numerous small genomic regions where all live-bearers carry the same core haplotype. Candidate regions show evidence for live-bearer–specific positive selection and are enriched for genes that are differentially expressed between egg-laying and live-bearing reproductive systems. Ages of selective sweeps suggest that live-bearer–specific alleles accumulated over more than 200,000 generations. Our results suggest that new functions evolve through the recruitment of many alleles rather than in a single evolutionary step.

Discrete-to-continuum limits of optimal transport with linear growth on periodic graphs - Portinale, Lorenzo; Quattrocchi, Filippo (European Journal of Applied Mathematics)
We prove discrete-to-continuum convergence for dynamical optimal transport on Zd -periodic graphs with cost functional having linear growth at infinity. This result provides an answer to a problem left open by Gladbach, Kopfer, Maas, and Portinale (Calc Var Partial Differential Equations 62(5), 2023), where the convergence behaviour of discrete boundary-value dynamical transport problems is proved under the stronger assumption of superlinear growth. Our result extends the known literature to some important classes of examples, such as scaling limits of 1 -Wasserstein transport problems. Similarly to what happens in the quadratic case, the geometry of the graph plays a crucial role in the structure of the limit cost function, as we discuss in the final part of this work, which includes some visual representations.

Variational structures for the Fokker-Planck equation with general Dirichlet boundary conditions - Quattrocchi, Filippo (arXiv)
We prove the convergence of a modified Jordan--Kinderlehrer--Otto scheme to a solution to the Fokker--Planck equation in $Ω \Subset \mathbb{R}^d$ with general, positive and temporally constant, Dirichlet boundary conditions. We work under mild assumptions on the domain, the drift, and the initial datum. In the special case where $Ω$ is an interval in $\mathbb{R}^1$, we prove that such a solution is a gradient flow -- curve of maximal slope -- within a suitable space of measures, endowed with a modified Wasserstein distance. Our discrete scheme and modified distance draw inspiration from contributions by A. Figalli and N. Gigli [J. Math. Pures Appl. 94, (2010), pp. 107--130], and J. Morales [J. Math. Pures Appl. 112, (2018), pp. 41--88] on an optimal-transport approach to evolution equations with Dirichlet boundary conditions. Similarly to these works, we allow the mass to flow from/to the boundary $\partial Ω$ throughout the evolution. However, our leading idea is to also keep track of the mass at the boundary by working with measures defined on the whole closure $\overline Ω$. The driving functional is a modification of the classical relative entropy that also makes use of the information at the boundary. As an intermediate result, when $Ω$ is an interval in $\mathbb{R}^1$, we find a formula for the descending slope of this geodesically nonconvex functional.
Keywords: gradient flows; Jordan–Kinderlehrer–Otto scheme; curves of maximal slope; optimal transport; Dirichlet boundary conditions; Fokker–Planck equation

Asymptotics for optimal empirical quantization of measures - Quattrocchi, Filippo (arXiv)
We investigate the minimal error in approximating a general probability measure $μ$ on $\mathbb{R}^d$ by the uniform measure on a finite set with prescribed cardinality $n$. The error is measured in the $p$-Wasserstein distance. In particular, when $1\le p<d$, we establish asymptotic upper and lower bounds as $n → ∞$ on the rescaled minimal error that have the same, explicit dependency on $μ$. In some instances, we prove that the rescaled minimal error has a limit. These include general measures in dimension $d = 2$ with $1 \le p < 2$, and uniform measures in arbitrary dimension with $1 \le p < d$. For some uniform measures, we prove the limit existence for $p \ge d$ as well. For a class of compactly supported measures with H\"older densities, we determine the convergence speed of the minimal error for every $p \ge 1$. Furthermore, we establish a new Pierce-type (i.e., nonasymptotic) upper estimate of the minimal error when $1 \le p < d$. In the initial sections, we survey the state of the art and draw connections with similar problems, such as classical and random quantization.
Keywords: optimal empirical quantization; vector quantization; Wasserstein distance; semidiscrete optimal transport; Zador’s Theorem; Pierce’s Lemma

GABAB receptors induce phasic release from medial habenula terminals through activity-dependent recruitment of release-ready vesicles - Koppensteiner, Peter; Bhandari, Pradeep; Önal, Hüseyin C; Borges Merjane, Carolina; Le Monnier, Elodie; Roy, Utsa; Nakamura, Yukihiro; Sadakata, Tetsushi; Sanbo, Makoto; Hirabayashi, Masumi; Rhee, JeongSeop; Brose, Nils; et al. (Proceedings of the National Academy of Sciences of the United States of America)
GABAB receptor (GBR) activation inhibits neurotransmitter release in axon terminals in the brain, except in medial habenula (MHb) terminals, which show robust potentiation. However, mechanisms underlying this enigmatic potentiation remain elusive. Here, we report that GBR activation on MHb terminals induces an activity-dependent transition from a facilitating, tonic to a depressing, phasic neurotransmitter release mode. This transition is accompanied by a 4.1-fold increase in readily releasable vesicle pool (RRP) size and a 3.5-fold increase of docked synaptic vesicles (SVs) at the presynaptic active zone (AZ). Strikingly, the depressing phasic release exhibits looser coupling distance than the tonic release. Furthermore, the tonic and phasic release are selectively affected by deletion of synaptoporin (SPO) and Ca 2+ -dependent activator protein for secretion 2 (CAPS2), respectively. SPO modulates augmentation, the short-term plasticity associated with tonic release, and CAPS2 retains the increased RRP for initial responses in phasic response trains. The cytosolic protein CAPS2 showed a SV-associated distribution similar to the vesicular transmembrane protein SPO, and they were colocalized in the same terminals. We developed the “Flash and Freeze-fracture” method, and revealed the release of SPO-associated vesicles in both tonic and phasic modes and activity-dependent recruitment of CAPS2 to the AZ during phasic release, which lasted several minutes. Overall, these results indicate that GBR activation translocates CAPS2 to the AZ along with the fusion of CAPS2-associated SVs, contributing to persistency of the RRP increase. Thus, we identified structural and molecular mechanisms underlying tonic and phasic neurotransmitter release and their transition by GBR activation in MHb terminals.

Emergent macroscopic bistability induced by a single superconducting qubit - Sett, Riya; Hassani, Farid; Phan, Duc T; Barzanjeh, Shabir; Vukics, Andras; Fink, Johannes M (PRX Quantum)
The photon blockade breakdown in a continuously driven cavity QED system has been proposed as a prime example for a first-order driven-dissipative quantum phase transition. However, the predicted scaling from a microscopic behavior—dominated by quantum fluctuations—to a macroscopic one—characterized by stable phases—and the associated exponents and phase diagram have not been observed so far. In this work we couple a single transmon qubit with a fixed coupling strength 𝑔 to a superconducting cavity that is in situ bandwidth 𝜅 tunable to controllably approach this thermodynamic limit. Even though the system remains microscopic, we observe its behavior becoming increasingly macroscopic as a function of 𝑔/𝜅. For the highest realized 𝑔/𝜅 of approximately 287, the system switches with a characteristic timescale as long as 6 s between a bright coherent state with approximately 8×103 intracavity photons and the vacuum state. This exceeds the microscopic timescales by 6 orders of magnitude and approaches the perfect hysteresis expected between two macroscopic attractors in the thermodynamic limit. These findings and interpretation are qualitatively supported by neoclassical theory and large-scale quantum-jump Monte Carlo simulations. Besides shedding more light on driven-dissipative physics in the limit of strong light-matter coupling, this system might also find applications in quantum sensing and metrology.

Data Analysis files for "Emergent Macroscopic Bistability Induced by a Single Superconducting Qubit" - Sett, Riya; Hassani, Farid; Phan, Duc T; Barzanjeh, Shabir; Vukics, Andras; Fink, Johannes M
Data analysis files for the manuscript "Emergent Macroscopic Bistability Induced by a Single Superconducting Qubit". This contains the raw data and the data analysis files for generating the figures in the manuscript. Figure1 file - The raw data of cavity transmission spectra for 6 different kappas are there. They are fitted with input-output theory in the python file. Figure2 file - The raw data at 8 MHz kappa are included. all hte figures in figure 2 are generated in the python file Figure3 file - The raw data of PBB single shot measurements at all kappas are included. The detailed analysis and the Figure3 generated for the paper are all in the python analysis file. Also, thefiles containing the time-evolution of the intensity from Master Equation solution are included. Figure4 file - The raw data at 2.6 MHz for different drive detunings and the corresponding analyses are included. And the python file includes the analysis of the experimental data as well as approximate neoclassical equations solutions for 2-level and 3-level transmons are included.

Developmental transformation of Ca2+ channel-vesicle nanotopography at a central GABAergic synapse - Chen, JingJing; Kaufmann, Walter; Chen, Chong; Arai, Itaru; Kim, Olena; Shigemoto, Ryuichi; Jonas, Peter M (Neuron)
The coupling between Ca2+ channels and release sensors is a key factor defining the signaling properties of a synapse. However, the coupling nanotopography at many synapses remains unknown, and it is unclear how it changes during development. To address these questions, we examined coupling at the cerebellar inhibitory basket cell (BC)-Purkinje cell (PC) synapse. Biophysical analysis of transmission by paired recording and intracellular pipette perfusion revealed that the effects of exogenous Ca2+ chelators decreased during development, despite constant reliance of release on P/Q-type Ca2+ channels. Structural analysis by freeze-fracture replica labeling (FRL) and transmission electron microscopy (EM) indicated that presynaptic P/Q-type Ca2+ channels formed nanoclusters throughout development, whereas docked vesicles were only clustered at later developmental stages. Modeling suggested a developmental transformation from a more random to a more clustered coupling nanotopography. Thus, presynaptic signaling developmentally approaches a point-to-point configuration, optimizing speed, reliability, and energy efficiency of synaptic transmission.